2009
DOI: 10.1128/ec.00110-09
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Capture of Viral and Plasmid DNA by Yeast Nuclear Chromosomes

Abstract: A 10-kb region of the nuclear genome of the yeast Vanderwaltozyma polyspora contains an unusual cluster of five pseudogenes homologous to five different genes from yeast killer viruses, killer plasmids, the 2m plasmid, and a Penicillium virus. By further database searches, we show that this phenomenon is not unique to V. polyspora but that about 40% of the sequenced genomes of Saccharomycotina species contain integrated copies of genes from DNA plasmids or RNA viruses. We propose the name NUPAVs (nuclear seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 71 publications
6
67
0
Order By: Relevance
“…Transfer from nonretroviral RNA viruses to cells is thought to be extremely rare (5,19). However, several very recent cases of eukaryotes in which nonretroviral integrated RNA viruses (NIRVs) were detected (17,27,36,60,61) suggest that transfer from nonretroviral RNA viruses to cells might be much more common than previously thought. In the present study, we analyzed eukaryotic genome databases for the presence of dsRNA virus-related sequences, and we present evidence that totiviral and partitiviral genes are transferred frequently into the nuclear genomes of eukaryotes and that some transferred genes even have functions in the recipient genomes.…”
mentioning
confidence: 77%
“…Transfer from nonretroviral RNA viruses to cells is thought to be extremely rare (5,19). However, several very recent cases of eukaryotes in which nonretroviral integrated RNA viruses (NIRVs) were detected (17,27,36,60,61) suggest that transfer from nonretroviral RNA viruses to cells might be much more common than previously thought. In the present study, we analyzed eukaryotic genome databases for the presence of dsRNA virus-related sequences, and we present evidence that totiviral and partitiviral genes are transferred frequently into the nuclear genomes of eukaryotes and that some transferred genes even have functions in the recipient genomes.…”
mentioning
confidence: 77%
“…Dramatic examples of PSDs are the killer plasmids of bacteria and yeast (63). In killer plasmids, the longer persistence of the encoded toxin relative to the antidote protein ensures that daughter cells die if the plasmid is lost.…”
Section: Types Of Sges and Their Consequencesmentioning
confidence: 99%
“…PSDs may have been co-opted by bacterial and yeast genomes for defense against competitors, viral protection, or other phenotypes. For example, killer plasmids share some features with bacteriocins in bacteria and diffusible killer toxins in yeast, which can act to kill competitor cells lacking the linked modification-rescue mechanism (63). Bacteriocins typically produce diffusible toxins, however, and therefore target different cell lineages.…”
Section: Types Of Sges and Their Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, a 10-kb chromosomal segment flanking a tRNA gene in a conserved syntenic region was found to contain 5 pseudogenes homologous in sequence to plasmid and viral genes from fungi. Subsequently, a systematic search within yeast and fungal genome sequences from public databases, using sequences of known extrachromosomal elements as queries, revealed that 42% of Saccharomycotina species (11 of 26 species tested) contain fragments of plasmid or viral origin (designated NUPAVs) integrated into their chromosomes (53). Most NUPAVs are pseudogenes, although one active gene, KHS1, encoding a killer factor, was also found in S. cerevisiae.…”
Section: Interspecific Exchanges Of Nonchromosomal Elementsmentioning
confidence: 99%